The state of innovation in coffee value chains and policy implication promoting innovation - Kien, Nguyen Trung; Long, Nguyen The (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
This study provides some initial review of demand and directions for innovation in coffee value chain (coffee enterprises and farmers in the enterprises’ value chain), the manner of interactive learning to enhance innovation capacity; and interaction among coffee enterprises, coffee farmers (production system), agricultural research system, extension system and education system. Finally, the study proposes policy implications to promote innovation. Code: 19120201